Baseline mortality-adjusted survival in colon cancer patients - Ukegjini, Kristjan; Warschkow, René; Marti, Lukas (Langenbeck's archives of surgery, 2016)
Background: This investigation assessed the baseline mortality-adjusted survival after colon cancer resection. Material and methods: In total, 523 patients with adenocarcinoma of the colon who underwent primary colon resection at Kantonsspital St. Gallen, Switzerland, between 1996 and 2008 were included. Results: The median follow-up was 25 months for all patients and 39 months for those who survived until the end of the follow-up. The 5-year relative survival rate was 63.2 % (95 % CI 57.3-69.6 %), and the overall survival rate was 52 % (95 % CI 47.6-57.7 %). After curative resection of stage I-III colon cancer, 40 % of the observed deaths were cancer-related and 60 % reflected the baseline mortality. In stage I, the 5-year relative survival was 103.2 % (95 % CI 91.4-116.5 %) and was not different from a matched population (p = 0.820). In multivariate analysis, good general health and less advanced cancer stages were associated with better relative and overall survival rates. A more advanced age was associated with better relative survival, but worse overall survival. Conclusions: The analysis of relative survival of patients exclusively with colon cancer revealed that prognosis of patients suffering from stage I colon cancer does not differ significantly from that of the general population. In more advanced stages, a relevant fraction of deaths is not cancer-related. As the stage determines a patient’s survival, early diagnosis is crucial for prognosis.
Gesehen am 15.08.2019